2020
DOI: 10.1186/s13054-019-2718-9
|View full text |Cite
|
Sign up to set email alerts
|

Brainstem dysfunction in critically ill patients

Abstract: The brainstem conveys sensory and motor inputs between the spinal cord and the brain, and contains nuclei of the cranial nerves. It controls the sleep-wake cycle and vital functions via the ascending reticular activating system and the autonomic nuclei, respectively. Brainstem dysfunction may lead to sensory and motor deficits, cranial nerve palsies, impairment of consciousness, dysautonomia, and respiratory failure. The brainstem is prone to various primary and secondary insults, resulting in acute or chronic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
67
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(67 citation statements)
references
References 88 publications
0
67
0
Order By: Relevance
“…Earlier studies from our group suggested that the MBT, which detects subtle motor behaviors missed by the CRS-R, can clinically discriminate patients with potential [19,20] Cranial nerve palsies Imaging (MRI)-brain-stem nuclear or nerve lesions Non convulsive status epilepticus Staring, eye deviations, neglect, myoclonus EEG-epileptic potentials Cortical blindness [12,13] Absence of visual interaction, absence of menace reflex, absence of visual pursuit Imaging (MRI)-bilateral occipital lesions Akinetic (frontal) Syndrome [18] Marked reduction of spontaneous movement and speech production with inconstant visual fixation and tracking, inconstant commandfollowing and vocalization…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies from our group suggested that the MBT, which detects subtle motor behaviors missed by the CRS-R, can clinically discriminate patients with potential [19,20] Cranial nerve palsies Imaging (MRI)-brain-stem nuclear or nerve lesions Non convulsive status epilepticus Staring, eye deviations, neglect, myoclonus EEG-epileptic potentials Cortical blindness [12,13] Absence of visual interaction, absence of menace reflex, absence of visual pursuit Imaging (MRI)-bilateral occipital lesions Akinetic (frontal) Syndrome [18] Marked reduction of spontaneous movement and speech production with inconstant visual fixation and tracking, inconstant commandfollowing and vocalization…”
Section: Discussionmentioning
confidence: 99%
“…4 The increase of mean arterial pressure (MAP) during endotracheal suctioning (total N = 1080 episodes) was not significantly different across patients with good or poor outcome (P > 0.2). mRS, modified Rankin Scale Score value of comatose patients [29]. In a recent study conducted in patients after cardiac arrest, reduced quantitative pupillary light reflex performed well in mortality prediction [30].…”
Section: Discussionmentioning
confidence: 98%
“…Surface EEG in unresponsive patients may help to identify patients with brain activity despite missing motor behavior [3]. Besides that, neurophysiological studies with evoked potentials and brain imaging such as MRI are used to estimate patients' outcomes [29]. Testing of ANS is a further cornerstone in prognostication of severely brain-injured patients.…”
Section: Discussionmentioning
confidence: 99%
“…Measuring the peripheral oxygen level is very important for any COVID-19 patient, as several reports suggest patients with minimal symptoms but with very critical oxygen level (49,50). Brainstem dysfunction also results in altered sleep-wake cycles and compromised autonomous control of the immune, circulatory, digestive, and respiratory systems (51). Brain inflammation encephalitis accompanied with seizures has also been reported (52).…”
Section: Effect On the Central And Peripheral Nervous Systemsmentioning
confidence: 99%